Longitudinal Growth and Body Composition of Twins versus Singletons in the First Month of Life. (24th December 2013) - Paviotti, Giulia; De Cunto, Angela; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio
Abstract : Background . Although twin gestation is well recognized to be associated with impaired fetal and postnatal growth, specific data about body composition of twins in the first month of life are scarce. Objective . The aim of this study was to compare the body composition of twins, evaluated with air-displacement plethysmography, to that of singletons of similar gestational age and adequacy of growth, during the first month of life. We tested the hypothesis that the quality of growth would be similar. Methods . Anthropometric and air-displacement plethysmography measurements were performed in 18 pairs of twins and in 36 singleton neonates, longitudinally, from birth to the 30th day of life. Each twin was matched to a singleton infant of similar gestational age and birth weight z -score. Results . With regard to anthropometric measures, the only difference was a lower weight in twins versus singletons on the 15th day of life. With regard to body composition, we did not find any difference between groups at any time point. Fat mass increased significantly from day 1 to day 30 in both twins and singletons. Conclusion . In terms of body composition, twins do not differ from singletons of similar gestational age and weight, either at birth or in early postnatal life.